2019
DOI: 10.3390/antiox8100483
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI-QTOF/MS Characterization of Phenolic Compounds in Palm Fruits (Jelly and Fishtail Palm) and Their Potential Antioxidant Activities

Abstract: Palm fruits have gained growing attention for their nutrition values and health promotion perspectives. They have a diverse range of bioactive compounds including carotenoids, vitamins, dietary fibres and especially polyphenolic compounds. These polyphenolic compounds contribute to the putative health benefits of palm fruits. Nevertheless, the detailed information about these polyphenols in palm fruits is limited. The present work was conducted to comprehensively characterize polyphenols in two palm fruits, je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
(80 reference statements)
1
33
0
1
Order By: Relevance
“…Most of the hydroxyphenylpropanoic acids and hydroxyphenylacetic acids were detected for the first time in stone fruits waste. Two out of three hydroxyphenylpropanoic acid derivatives (Compound 24, 25 ) were detected only in peach and have been reported in palm fruit [ 40 ]. Dihydroferulic acid 4 -O- glucuronide (Compound 23 ) was reported in Opuntia ficus-indica fruit with antioxidant potential by Aruwa, et al [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the hydroxyphenylpropanoic acids and hydroxyphenylacetic acids were detected for the first time in stone fruits waste. Two out of three hydroxyphenylpropanoic acid derivatives (Compound 24, 25 ) were detected only in peach and have been reported in palm fruit [ 40 ]. Dihydroferulic acid 4 -O- glucuronide (Compound 23 ) was reported in Opuntia ficus-indica fruit with antioxidant potential by Aruwa, et al [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…HPLC-PDA was carried out by using the method of Ma, et al [ 40 ] to quantify the targeted phenolic compounds in stone fruits samples, which was performed with Agilent 1200 series HPLC (Agilent Technologies, CA, USA) equipped with a photodiode array (PDA) detector. Column and LC conditions were maintained as described above in LC-ESI-QTOF-MS/MS analysis except the sample injection volume is changed to 20 µL.…”
Section: Methodsmentioning
confidence: 99%
“…The separation and characterization of phenolics were conducted by adopting our previously published method of Zhong, et al [21], elaborated in the supplementary material. However, for the quantification of targeted phenolics present in different fruit peel samples was achieved with an Agilent 1200 HPLC coupled with a photodiode array (PDA) detector by following the protocol of Ma, et al [22], explained in the supplementary material.…”
Section: Characterization and Quantification Of Phenolics Using Lc-esmentioning
confidence: 99%
“…The screening and characterization of polyphenolic compounds showed that some of the polyphenols presented in these seaweeds have strong antioxidant potential. Hydroxycinnamic acid derivatives, hydroxybenzoic acids and their derivatives, protocatechuic acid, anthocyanins, flavonoids and their derivatives, hydroxybenzaldehydes, hydroxytyrosol, phloroglucinol and quercetin derivatives are regarded as potential compounds showing considerable free radical scavenging capacity [66][67][68][69][70][71]. The presence of these antioxidant compounds indicates that seaweeds can be good sources of polyphenols and could be utilized in food, feed, and pharmaceutical industries.…”
Section: Lignansmentioning
confidence: 99%
“…LC-ESI-QTOF-MS/MS analysis was performed with an Agilent 1200 series HPLC (Agilent Technologies, Santa Clara, CA, USA) equipped with an Agilent 6520 Accurate-Mass Q-TOF LC-MS (Agilent Technologies, Santa Clara, CA, USA) via an electrospray ionization source (ESI). The separation was achieved by a Synergi Hydro-RP 80 Å, LC Column (250 mm × 4.6 mm, 4 µm) (Phenomenex, Lane Cove, NSW, Australia) at room temperature and the sample temperature was set at 10 • C. LC-MS/MS analysis were performed by modifying the method of Chao et al [66]. The mobile phase consisted of water/acetic acid (98:2, v/v; eluent A) and acetonitrile/acetic acid/ water (50:0.5:49.5, v/v/v; eluent B).…”
Section: Lc-esi-qtof-ms/ms Characterization Of Phenolic Compoundsmentioning
confidence: 99%